The Pickwick murders - Redmond, Heather, 1969- (Redmond, Heather, 1969- Dickens of a crime., 2021)
When his initiation into the Lightning Club takes a murderous turn, Charles Dickens is accused of the crime and is locked away in Newgate Prison where he must rely on his fiancé and her sleuthing skills to save him from the hangman's noose.